Key Factors Shaping Academic Job Performance in Malaysian Higher Education - Kok Ban Teoh; Cherian Mohan; Yeok Han Wong; Jia Yang Wu; Yi Han Wu; Yun Han Wu; Daisy Mui Hung Kee (AIBPM Publisher, 2026)
This study investigates the factors that influence academic job performance among lecturers in Malaysian higher education institutions (HEIs). According to the theories from organizational psychology and higher education research, the study examined four key predictors, which are personality traits (conscientiousness and openness), motivation, lecturer professional autonomy, and transformational leadership. The study used the quantitative research design by using an online questionnaire, and a total of 150 valid responses were collected from lecturers across Malaysian HEIs. The data were analyzed by using descriptive statistics and correlational analysis to determine the relationships between variables. The findings are expected to provide insights on how individual dispositions, internal motivation, workplace autonomy, and leadership practices collectively shape lecturer's performance. To provide a useful implication for institutional policies, lecturer development, and leadership practices, this study will contribute to a deeper understanding of performance determinants in the Malaysian higher education context.